PAK Paradox: Paramecium Appears To Have More K(+)-Channel Genes than Humans - Haynes, W. John (American Society for Microbiology, 2003)
K(+)-selective ion channels (K(+) channels) have been found in bacteria, archaea, eucarya, and viruses. In Paramecium and other ciliates, K(+) currents play an essential role in cilia-based motility. We have retrieved and sequenced seven closely related Paramecium K(+)-channel gene (PAK) sequences by using previously reported fragments. An additional eight unique K(+)-channel sequences were retrieved from an indexed library recently used in a pilot genome sequencing project. Alignments of these protein translations indicate that while these 15 genes have diverged at different times, they all maintain many characteristics associated with just one subclass of metazoan K(+) channels (CNG/ERG type). Our results indicate that most of the genes are expressed, because all predicted frameshifts and several gaps in the homolog alignments contain Paramecium intron sequences deleted from reverse transcription-PCR products. Some of the variations in the 15 genomic nucleotide sequences involve an absence of introns, even between very closely related sequences, suggesting a potential occurrence of reverse transcription in the past. Extrapolation from the available genome sequence indicates that Paramecium harbors as many as several hundred of this one type of K(+)-channel gene. This quantity is far more numerous than those of K(+)-channel genes of all types known in any metazoan (e.g., ∼80 in humans, ∼30 in flies, and ∼15 in Arabidopsis). In an effort to understand this plurality, we discuss several possible reasons for their maintenance, including variations in expression levels in response to changes in the freshwater environment, like that seen with other major plasma membrane proteins in Paramecium.